Osseous manifestations of 'handball goalie's elbow' - Tyrdal, S.; Finnanger, A. M. (Scandinavian Journal of Medicine & Science in Sports, 1999)
The radiographic manifestations of musculoskeletal stress at the elbow associated with European team handball are reported in 46 amateur handball players with 74 elbows injured by blocking shots. All the 92 elbows were evaluated by clinical and radiological examinations using the 18 asymptotic elbows as a control. Lateral and anterioposterior radiographs were obtained of both elbows in addition to stress radiographs with manual valgus force. The mean age of the athletes was 23.0 (range 16-44) years. The players had an athletic experience of 11.6 years (range 3.5-34). Their elbow pain had at inclusion lasted for 43 +/- 42) (range 2-252) months. Their symptoms were located in all four parts of the elbow and in different combinations: anterior (6), posterior (23), medial (38), lateral (17), and in the whole elbow (3). No major bony lesions were found. Minor abnormalities were observed (21%), including loose bodies (7), traction spur formation (1), and minor arthritic changes (7) in addition to medial instability (12). Manual instability stress test was not useful and should be performed with a stress device. 'Handball goalie's elbow' does not lead to major osseous manifestations. Scand J Med Sci Sports 1999 Apr;9(2):92-7